Macleod's Clinical OSCEs / Paul O Neill, Tim Pattison, ALexandra Evans, Meriel Tolhurst-Cleaver, Serena Tolhurst-Cleaver. - Neill, Paul O; Pattison, Tim; Evans, ALexandra; Tolhurst-Cleaver, Meriel; Tolhurst-Cleaver, Serena (London : Elsevier, 2016)
This study guide for students revising for clinical OSCE exams contains over 60 of the most commonly encountered OSCE stations in medicine and surgery, arranged according to type of skill - for example, history-taking, ethics and communication, and physical examinations. With simple advice, tips about preparation and easily understood explanations, it includes sample OSCE station questions and simulated patient scripts (with answers) for practice at home
Keywords: OCCE; Clinical medicine -- Examinations; Study guides; Clinical Competence Physical Examination; Clinical Examinations